ISLAMIC RELIGIOUS LEADERS’ PERCEPTION OF TAX OBLIGATION IN DEPOK INDONESIA - Adang Hendrawan; Ismail Khozen; Milla Sepliana Setyowati; Arfah Habib Saragih (Journal of Islamic, Social, Economics and Development, 2019)
Religious leaders have high social standing in Indonesian society. Their words, deeds, and behavior are source of exemplary conduct of the society. They are perceived to have better religious understanding than average people do. In the relation between religious affairs and taxation, different opinions come up in society regarding tax obligation. The difference is generally caused by religious leaders’ different interpretation of whether there are obligations for Muslims other than zakat. This difference has led to a discourse, so it is considered important for the issue to be studied. For that reason, this study tries to find out Islamic religious leaders’ perceptions of tax obligations. This study employs quantitative approach and it is categorized as cross-sectional research. Data were collected by distributing questionnaires to Islamic religious leaders in the city of Depok Indonesia. The results of this study indicate that leaders of pesantren in Depok, as representatives of Islamic religious leaders, have positive perception of tax obligations. In other words, they particularly do not have any objection to tax obligations.